Managing congestive heart failure in a general hospital in Malaysia. Are we keeping pace with evidence? - Chin, S P; Sapari, Satwi; How, Soon Hin; Sim, K. H. (Malaysian Medical Association, 2006)
Evidence-based heart failure management now includes beta-blockers and spironolactone in addition to diuretics and angiotensin-converting enzyme inhibitors. We aim to determine if these recommendations had been applied in practice for acute and chronic stable heart failure, and what difficulties there might be. Data from 80 consecutive patients hospitalized for decompensated heart failure ('acute') between May and July 2003 were analyzed at admission, upon discharge and at 12 weeks follow-up; along with 74 cardiology clinic out-patients with stable congestive heart failure ('chronic'- no decompensation or admission in previous six months). Less than half of study patients with prior left ventricular dysfunction were on ACE-inhibitors (47%), diuretics (39%), ATII antagonists, spironolactone or digoxin (5% each). All 'acute' patients were commenced on diuretics and ACE-inhibitors in hospital. Six patients died or transferred to another center. Compliance with clinic appointment at 12 weeks was 85% despite telephone reminders. Drug prescription at 12 weeks was significantly lower for diuretics and ACE-inhibitors compared to prescription at discharge (all p < 0.05) but higher compared to patients with chronic HF. Diuretics and ACE inhibitors remain under-utilized for patients with recurrent heart failure. Use of spironolactone and beta-blocker is slow due to limited medical experience and funding. Clinic non-attendance is significant and due to patient factors.